Lipoprotein Metabolism, Dyslipidemia, and Lipid-Lowering Therapy in Women: A Comprehensive Review - Jakub Michal Zimodro; Magda Mucha; Heiner K. Berthold; Ioanna Gouni-Berthold (MDPI AG, 2024)
Lipid-lowering therapy (LLT) is a cornerstone of atherosclerotic cardiovascular disease prevention. Although LLT might lead to different reductions in low-density lipoprotein cholesterol (LDL-C) levels in women and men, LLT diminishes cardiovascular risk equally effectively in both sexes. Despite similar LLT efficacy, the use of high-intensity statins, ezetimibe, and proprotein convertase subtilisin/kexin type 9 inhibitors is lower in women compared to men. Women achieve the guideline-recommended LDL-C levels less often than men. Greater cholesterol burden is particularly prominent in women with familial hypercholesterolemia. In clinical practice, women and men with dyslipidemia present with different cardiovascular risk profiles and disease manifestations. The concentrations of LDL-C, lipoprotein(a), and other blood lipids differ between women and men over a lifetime. Dissimilar levels of LLT target molecules partially result from sex-specific hormonal and genetic determinants of lipoprotein metabolism. Hence, to evaluate a potential need for sex-specific LLT, this comprehensive review (i) describes the impact of sex on lipoprotein metabolism and lipid profile, (ii) highlights sex differences in cardiovascular risk among patients with dyslipidemia, (iii) presents recent, up-to-date clinical trial and real-world data on LLT efficacy and safety in women, and (iv) discusses the diverse medical needs of women and men with dyslipidemia and increased cardiovascular risk.